Teacher training: abp with a focus on the eja student life project via distance learning - Oliveira, Laôr Fernandes de; Chida, Rossana Ishii (Universidade Federal de São Carlos, 2024)
This article aims to present the training of Distance Learning Youth and Adult Education teachers at Sesi-SP regarding the possibility of working with students’ life projects, through Project-Based Learning (PBL). The purpose was to make teachers aware of the importance of collective and interdisciplinary projects, carried out remotely, with EJA students. The effective involvement of teachers and a change in their outlook regarding carrying out projects in their classroom environment was observed.
Keywords: Distance education; Youth and adult education; Teacher training; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM